The squat lobster genus Phylladiorhynchus Baba, 1969 in New Zealand and eastern Australia, with description of six new species - Schnabel, Kareen E.; Ahyong, Shane T. (Zootaxa, 2019)
The small galatheid squat lobster genus Phylladiorhynchus currently contains five species, three of which supposedly have wide Indo-Pacific distributions. To date, two putatively widespread species, P. pusillus and P. integrirostris have been recorded from New Zealand and Australian waters. Here, we review the New Zealand and eastern Australian species of Phylladiorhynchus based on extensive collections from the region using morphological and molecular data. The type species, P. pusillus (Henderson, 1885) (type locality: Twofold Bay, Australia) is redescribed and shown to occur on both sides of the Tasman Sea. Phylladiorhynchus integrirostris, for which the original Hawaiian type material has been lost, is redescribed based on a neotype and shown not to occur in New Zealand or Australian waters, previous records being referable to other species. Six new species of Phylladiorhynchus are described. Seven species of Phylladiorhynchus are now known from New Zealand and eastern Australia. A key to all species of the genus is provided. Results of the present study show that the regional diversity of Phylladiorhynchus is significantly higher than previously reported and demonstrates the utility of a number of subtle morphological characters as diagnostic of species.